1999
DOI: 10.1002/(sici)1097-0185(19990701)255:3<252::aid-ar2>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of the mitral valve is strikingly depleted with age

Abstract: Previous reports demonstrated that mammalian atrioventricular (AV) valves possess a dense nerve plexus, consisting of nerve subpopulations which differ from each other in densities and patterns of distribution in the valves, and which may have sensory or motor roles in valve function. Although there is extensive evidence that age-related changes occur in autonomic nerves of animals and humans (Daly et al. that these changes contribute to changes in cardiac function (Klausner and Schwartz Clin. Geriat. Med., 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In the normal mitral valve, an extensive plexus of nerves innervates the basilar region of the valve nearest the atrioventricular ring, whereas the free leaflet edges are relatively devoid of nerve endings. 45 This pattern is largely maintained in humans with mitral valve prolapse. 46 The exact function of valvular nerve tissue is unknown but may involve mechanoreception, active valve contraction, arrhythmogenesis, or transmission of the hyperadrenergic heart failure state directly to valve tissue.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the normal mitral valve, an extensive plexus of nerves innervates the basilar region of the valve nearest the atrioventricular ring, whereas the free leaflet edges are relatively devoid of nerve endings. 45 This pattern is largely maintained in humans with mitral valve prolapse. 46 The exact function of valvular nerve tissue is unknown but may involve mechanoreception, active valve contraction, arrhythmogenesis, or transmission of the hyperadrenergic heart failure state directly to valve tissue.…”
Section: Discussionmentioning
confidence: 92%
“…46 The exact function of valvular nerve tissue is unknown but may involve mechanoreception, active valve contraction, arrhythmogenesis, or transmission of the hyperadrenergic heart failure state directly to valve tissue. 45,47 Proteolytic enzymes such as MMPs regulate turnover and remodeling of the valvular extracellular matrix. A previous study e reported increased expression of collagenase-type MMPs 1 and 13 in dogs with DMVD.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 In rats, both sensory and motor type of nerves were markedly diminished in older animals. 31 There was no difference in mitral valve nerve density between young dogs aged 6–12 months and adult dogs aged 5 years, but there was a significant reduction in mitral valve nerve density in dogs above 10 years of age.…”
Section: Aging and Innervationmentioning
confidence: 98%
“…Nevertheless, from the available data, most studies support an age-related decrease in the density and distribution of nerves in heart valves [5,15]. These changes are seen both in the aortic and mitral valves [5,15]. The ageassociated changes are thought to affect cholinergic AchE nerve fibers more than adrenergic AchE nerve fibers (at least in the atrioventricular valves) [16].…”
Section: Factors Influencing Normal Nerve Distributionmentioning
confidence: 99%